Estudo da hipótese do 'ciclo de vida' de modigliani-brumberg nas condições do Brasil - Coelho de Alvarenga, Sonia; Faria Potsch Magalhães, Gilson; Basílio C Seraphim, João; Hammerschidmdt, Benjamin (Revista Ceres, 2025)
Consumption is a very important factor in any economic analysis. The search for better standards of living is a most important target of governmental policies of any country and is directly related to higher levels of consumption. The objective oof this paper is the estimation of an aggregate consumption function using the model proposed by Modigliani-Brumberg. The empirical results utilizing data from National Accounts were not satisfactory. It seems that new studies in this area can be substantially improved by taking into account the inflation of the period.